Design of Web-Based Planned Referral Information System from Public Health Centers to Hospital (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2020)
The aim of the study was to create a web-based planned referral system (SIJUNA) to help manage referral services from public health centers to hospitals so that there was no reason for patients not to be served because the human resources and facilities needed were not available. This study uses action research with a qualitative approach and the system development stage using the FAST method. The system is tested using black box testing. The results of this study are the establishment SIJUNA that facilitates the referral process of patients from the Public Health Center to the Hospital. With the existence of SIJUNA, the operational needs of services are good with the types of outpatient referrals, inpatient care, and emergencies can be fulfilled by increasing accessibility such as certainty of service time with competence and the closest radius of the patient's location, equalizing and increasing the effectiveness of health services, nearest health who has competencies according to patient needs.